Conditions influencing the choice between direct shipment and transshipment in maritime shipping network - Hoshi Tagawa; Tomoya Kawasaki; Shinya Hanaoka (Journal of Shipping and Trade (JST), 2021)
This study examines the conditions that influence the choice between direct shipment and transshipment, focusing on two factors: geographical distance and demand. We develop a two-stage model comprising shipping lines and shippers, and apply it to a virtual maritime network with one origin, two destination ports, and one hub port. The generalized costs of shippers in the optimum direct shipment and in transshipment for the shipping lines model are compared to evaluate the choice between direct shipment and transshipment. We find that competitiveness of the port as a hub, indicating the cargo volume aggregated in transshipment, is essential for examining the cost-effectiveness of direct shipment and transshipment. The comparison between the cost-effectiveness of direct shipment and transshipment is based on the configuration of each network, especially in terms of frequency and the vessel size deployed. Direct shipment can be more cost-effective for short distances.
Keywords: 650; Direct shipment; Shipping network; Transshipment; Two-stage model